Assembling Surfactants-Mucoadhesive Polymer Nanomicelles (ASMP-Nano) for Ocular Delivery of Cyclosporine-A - Eleonora Terreni; Patrizia Chetoni; Silvia Tampucci; Susi Burgalassi; Ali Athab Al-kinani; Raid G. Alany; Daniela Monti (MDPI AG, 2020)
The physiological protective mechanisms of the eye reduce the bioavailability of topically administered drugs above all for those with high molecular weight and /or lipophilic characteristics, such as Cyclosporine A (CyA). The combined strategy based on the association of nanomicelles and mucoadhesive polymer seems promising since a limited number of commercial products containing CyA have been recently approved. The scope of this investigation was the design of Assembling Surfactants-Mucoadhesive Polymer Nanomicelles (ASMP-Nano), based on a binary system of two surfactants in combination with hyaluronic acid, and their biopharmaceutical evaluation. The optimisation of the ASMP-Nano in term of the amount of surfactants, CyA-loading and size determined the selection of the clear and stable Nano1HAB-CyA formulation containing 0.105% w/w CyA loaded-nanomicelles with a size of 14.41 nm. The nanostructured system had a protective effect towards epithelial corneal cells with a cell viability of more than 80%. It interacted with cellular barriers favouring the uptake and the accumulation of CyA into the cells as evidenced by fluorescent probe distribution, by hindering CyA permeation through reconstituted corneal epithelial tissue. In pharmacokinetics study on rabbits, the nanomicellar carrier prolonged the CyA retention time in the precorneal area mainly in presence of hyaluronic acid (HA), a mucoadhesive polymer.